State of Arizona, complainant, vs. State of California ... [et al.], defendants : United States of America, intervener : State of Nevada, intervener : petition for rehearing of decision denying motion to join the states of Colorado, New Mexico, Utah, and Wyoming. - Brown, Edmund G. (Edmund Gerald), 1905-1996; Ely, Northcutt, 1903-1997; McCarty, Robert L.; Moore, Prentiss; Nelson, Gilbert F.; Corker, Charles E.; Friedman, Howard I.; Gindler, Burton J.; McKenney, James B.; Alexander, John R.; Wheatley, Charles F.; Jenney, Francis E.; et al. ([publisher not identified], 1955)
Case summary: "Arizona v. California was a 12-year epic battle including three years of trial in front of a special master appointed by the U.S. Supreme Court. The trial involved 106 witnesses and hundreds of volumes of exhibits, ultimately producing a 433-page final report from the Master in December of 1960. Proceedings at the U.S. Supreme Court required two oral arguments, producing a 5-3 decision in 1963 with two dissenting opinions, with the majority opinion implemented by a decree in 1964. The case was an original action in the U.S. Supreme Court, with Arizona seeking to clarify its rights to the use of Colorado River basin water. It was filed 30 years after the seven basin states drafted the Colorado River Compact, which apportioned the waters of the basin roughly equally between the states of the Upper and Lower Divisions, but did not apportion shares to individual states. In addition to Arizona and California, Nevada, New Mexico, and Utah were party to the case because they had lands located within the Lower Basin. The United States was also party to the case because of the federal water projects and lands located within the Lower Basin. It was perhaps the most high profile water case ever to be decided by the U.S. Supreme Court and produced considerable commentary."-- Lawrence J. MacDonnell, Arizona v. California Revisited, 52 Nat. Resources J. 363, 365-66 (2012) (quoted with permission of the author)